Profitability, Liquidity, and Activity on Financial Perfomance with Firm Value as a Mediating Variable - dewi khinasih wahyuati dewi khinasih wahyuati; Umi Nadhiroh (LP2M IAIN Palopo, 2025)
This study aims to analyze the effect of profitability, liquidity, and activity on financial performance with firm value as a mediating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The research method used is panel data regression, classical assumption test, and Sobel test using the Random Effect Model and Common Effect Model approaches. The results of this study indicate that profitability (ROA) does not significantly affect financial performance (DER) and firm value (PBV), while liquidity (CR) has a significant negative effect on financial performance, indicating that companies with high liquidity tend to use less debt in their funding structure because they have a good ability to meet short-term obligations using their current assets. However, liquidity (CR) does not significantly affect firm value (PBV). Activity (TATO) does not affect financial performance (DER), but activity (TATO) has a significant positive effect on firm value (PBV). Firm value (PBV) has a significant positive effect on financial performance (DER). The Sobel test results indicate that firm value (PBV) is unable to mediate profitability, liquidity, and activity on financial performance.